The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1103/physrevb.89.054434
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of skyrmion lattices and bimerons in chiral magnetic thin films with nonmagnetic impurities

Abstract: Skyrmions are topologically protected field configurations with particle-like properties that play important roles in various fields of science. Recently, skyrmions have been directly observed in chiral magnets. Here, we investigate the effects of nonmagnetic impurities (structural point-like defects) on the different initial states (random or helical states) and on the formation of the skyrmion crystal in a discrete lattice. By using first-principle calculations and Monte Carlo techniques, we have shown that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 33 publications
1
26
0
2
Order By: Relevance
“…Any application involving the movement of skyrmions, such as skyrmion-based racetrack memories, will profit from the fact that extremely low spin-polarized currents are sufficient to drive skyrmions, as shown by numerical simulations 26,78 . However, it remains to be further experimentally investigated which type of defects may pin skyrmions in ultrathin films and multilayers [79][80][81][82] , leading to a modified behaviour compared to that predicted by theoretical models, which are usually based on ideal metal layer structures. In this respect, the comparison of experimental results obtained for epitaxially grown and sputter-deposited thin magnetic films and multilayer structures, as well as between polycrystalline and amorphous layers, can be very valuable-it can provide a deeper insight into the role of structural imperfections and spatial inhomogeneities of the relevant magnetic material parameters for the static properties and dynamic behaviour of nanoscale magnetic skyrmions.…”
Section: Towards Skyrmion-based Devicesmentioning
confidence: 99%
“…Any application involving the movement of skyrmions, such as skyrmion-based racetrack memories, will profit from the fact that extremely low spin-polarized currents are sufficient to drive skyrmions, as shown by numerical simulations 26,78 . However, it remains to be further experimentally investigated which type of defects may pin skyrmions in ultrathin films and multilayers [79][80][81][82] , leading to a modified behaviour compared to that predicted by theoretical models, which are usually based on ideal metal layer structures. In this respect, the comparison of experimental results obtained for epitaxially grown and sputter-deposited thin magnetic films and multilayer structures, as well as between polycrystalline and amorphous layers, can be very valuable-it can provide a deeper insight into the role of structural imperfections and spatial inhomogeneities of the relevant magnetic material parameters for the static properties and dynamic behaviour of nanoscale magnetic skyrmions.…”
Section: Towards Skyrmion-based Devicesmentioning
confidence: 99%
“…Since this initial discovery there has been tremendous growth in the field as an increasing number of materials have been found that can support a skyrmion phase [3][4][5][6][7][8][9][10] . There are also numerous proposals on how to stabilize skyrmion states by utilizing different materials properties or bilayers [11][12][13][14] . Direct imaging of skyrmions with Lorentz microscopy [3][4][5]7,10 and other techniques 8,15,16 show that the skyrmions form a triangular lattice and have particle-like properties similar to vortices in type-II superconductors 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Various stripes, including curved, ramified, maze, have long been observed in experiments and simulations [27][28][29][30][31][32][33][34], but there is no good description about those complex spin structures to date. For short race-track-like stripes, a notion of meron with ½ skyrmion number or bimeron [34][35][36] were used to describe one end or whole structure. This local description is not accurate and not necessary, an those bimerons should be correctly called skyrmions in order to reflect a holistic view of the spin structure.…”
Section: Discussionmentioning
confidence: 99%